The Digital Transformation of Tafsir and Its Implications for Islamic Legal Derivation in the Contemporary Era - Ali Sati; Abdul Halim; Abdul Hayy Nasution; Muhammad Ridwan (Faculty of Sharia, IAIN Metro, 2025)
The digitalization of Qur’anic interpretation has profoundly influenced the methodology of istinbat al-ahkam (deriving Islamic legal rulings), reshaping how scholars and legal institutions engage with classical texts in emerging digital platforms. This article explores the impact of selected tools—such as AI-driven tafsir platforms, semantic databases, and multimedia applications—on formulating Islamic legal reasoning in the digital era. Moving beyond a purely epistemological analysis, the study critically assesses how digital interfaces affect interpretive authority and methodological integrity and the production of contemporary legal responses to real-world issues, including Islamic digital finance, artificial intelligence ethics, and Sharia-based policymaking in digital environments. Utilizing a qualitative literature review combined with thematic content analysis, this research draws on classical sources and contemporary scholarship to investigate the shifting landscape of Islamic legal derivation in the digital age. Particular attention is given to the role of legal actors—such as fatwa councils, religious courts, and legislative bodies—in legitimizing or contesting digital tafsir outputs. The study applies maqasid al-shari’ah as developed by al-Shatibi as a normative framework to evaluate the legal-ethical implications of digital tafsir and its alignment with the objectives of protecting religion (din), intellect (‘aql), and public welfare (maslahah ‘ammah). Findings indicate that while digital tools significantly enhance accessibility, interactivity, and public engagement with Islamic texts, they also present challenges related to standardization, authenticity, and the erosion of traditional scholarly authority. This article offers a typology of digital influence—from functional assistance to epistemological disruption—and proposes practical pathways for integrating digital innovation within a framework of maqasid-oriented legal governance. The study contributes to the theoretical development of Islamic legal thought and the practical design of responsive, accountable, and ethically grounded legal frameworks for the digital era.